Sugarcane production and food security in Uganda - Guloba, Madina M.; Mbowa, Swaibu; Nakazi, Florence; Mather, David L.; Bryan, Elizabeth (Michigan State University Press, 2023)
This study investigates the relationship between farm household participation in sugarcane production and food security in the main sugarcane-producing sub-regions of Busoga, Buganda, and Bunyoro of Uganda. Analysis is based on primary data collected from 1,771 households in these regions as well as qualitative focus group discussions with cane growers. Descriptive analysis found that three different measures of food security -- Household Food Insecurity Access Score (HFIAS); Months of Adequate Household Food Provisioning (MAHFP); and Household Dietary Diversity Score (HDDS); revealed higher average values of HFIAS, MAHFP and HDDS for cane growing households compared to non-cane growers. Poisson regressions of the three food security measures (and an Ordered Probit Model of Food Insecurity Score, derived from HFIAS) found that farm households engaging in cane production in 2021 had lower levels of food insecurity and a higher number of months of food adequacy, on average, relative to households not producing cane, while controlling for other factors known to influence household food security. Maintaining the positive association between cane production and food security requires a policy environment and public sector governance to promote improved coordination between growers and millers and consideration of related income stabilisation mechanisms for sugarcane farmers. In addition, extension services should promote sugarcane production on farms with 8 or more acres only, farmer adherence to maintaining food crop cultivation, and use of productivity-enhancing technologies in cane and food crop production.